DUKUNGAN KELUARGA DAN TINGKAT KEPATUHAN MINUM OBAT PADA PASIEN DIABETES MELITUS TIPE 2 - Pramanda, Tasya; Wantonoro, Wantonoro; Asnindari, Lutfi Nurdian (Institut Teknologi dan Kesehatan Muhammadiyah Kalimantan Barat, 2026)
Background: Type 2 Diabetes Mellitus is a chronic disease that requires long-term treatment and high medication adherence to prevent complications. One factor that is thought to play a role in improving medication adherence is family support. Family support is expected to help patients adhere to regular medication use; however, in practice, medication adherence among patients with Type 2 Diabetes Mellitus is often found to be low.Objective: This study aimed to determine the relationship between family support and the level of medication adherence among patients with Type 2 Diabetes Mellitus at Gamping II Primary Health Center. Methods: This study employed a quantitative design with a cross-sectional approach. The sample consisted of 89 patients with Type 2 Diabetes Mellitus selected using a total sampling technique. Data were collected using a family support questionnaire and a medication adherence questionnaire. Data analysis was conducted using univariate and bivariate analyses with the Chi-Square test. Results: The results showed that most respondents had moderate family support (53.9%) and a low level of medication adherence (86.5%). The Chi-Square test yielded a p-value of 0.341 (p > 0.05), indicating that there was no significant relationship between family support and medication adherence among patients with Type 2 Diabetes Mellitus. Conclusion: The majority of patients with Type 2 Diabetes Mellitus at Gamping II Community Health Center have a moderate level of family support; however, their medication adherence remains low. Statistical analysis showed that there was no significant relationship between family support and medication adherence among patients with Type 2 Diabetes Mellitus (p > 0.05).